2020 IEEE 27th Symposium on Computer Arithmetic (ARITH) 2020
DOI: 10.1109/arith48897.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

A Hole in the Ladder : Interleaved Variables in Iterative Conditional Branching

Abstract: The modular exponentiation is crucial to the RSA cryptographic protocol, and variants inspired by the Montgomery ladder have been studied to provide more secure algorithms. In this paper, we abstract away the iterative conditional branching used in the Montgomery ladder, and formalize systems of equations necessary to obtain what we call the semi-interleaved and fully-interleaved ladder properties. In particular, we design fault-injection attacks able to obtain bits of the secret against semi-interleaved ladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The EnergyAnalyser tool [7] uses robust and accurate energy models [8], [9] for the target hardware platforms to predict the energy consumed by each task. The SecurityAnalyser quantifies the security protection level against timing and power side-channel attacks with novel metrics [10], and the SecurityOptimiser transforms the code, if required, to increase protection against these side-channel attacks [11], [12].…”
Section: A the Teamplay Methodology For Predictable Architecturesmentioning
confidence: 99%
“…The EnergyAnalyser tool [7] uses robust and accurate energy models [8], [9] for the target hardware platforms to predict the energy consumed by each task. The SecurityAnalyser quantifies the security protection level against timing and power side-channel attacks with novel metrics [10], and the SecurityOptimiser transforms the code, if required, to increase protection against these side-channel attacks [11], [12].…”
Section: A the Teamplay Methodology For Predictable Architecturesmentioning
confidence: 99%
“…Marquer and Richmond [28] showed that the algorithm in Listing 1 can be rewritten as the common left-to-right exponentiation in Listing 6. More generally, they studied programs with iterative conditional branching, e.g.…”
Section: Ladder Equationsmentioning
confidence: 99%
“…Joye [18,19] introduces highly regular right-to-left variants and left-to-right/right-to-left variants respectively, and Walter [39] demonstrates their duality. Marquer and Richmond [28] abstract away the algorithmic strength of the Montgomery ladder against SCAs, by defining semi-and fully-ladderisable programs. Brown et al [11] propose a Contract Specification Language (CSL), to allow the developer to capture non-functional properties (NFPs) about their program (including time and energy).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations